On the job search and the wage distribution - Bent Jesper Christensen; Dale Mortensen; George R. Neumann; Axel Werwatz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
The estimates of the structural parameters of a job separations model derived from the theory of on-the-job search are reported in this papers. Given that each employer pays the same wage to all observably equivalent workers and that wage dispersion across employers exists in the sense that different employers offer different wages to the same worker, the theory implies that a firms separations outflow is the sum of an exogenous flow to unemployment and a job-to-job flow that decreases with the employer's wage. We find that the model provides a good description of job separation flows in our cross-firm sample drawn from the Danish Pay and Performance database for the year 1994- 1995. The estimates also explain most and in some cases all of the employment effect, defined as the difference between median wage earned by employed workers and the median wage offered by employers. Finally, the empirical results also provide estimates of the curvature of the cost of search function as well as the parameters of the separations equations.
urn:nbn:de:kobv:11-10048343
Keywords: 330